Towards optimal diabetes therapy management: An evaluation of therapy algorithms for type 2 diabetes mellitus at community health centers (CHCs) in Makassar City, South Sula-wesi, Indonesia - Rusli Rusli; Nurisyah Nurisyah; Sisilia Teresia Rosmala Dewi; Alfrida Monica Salasa; Arisanty Arisanty; Dwi Syah Fitrah Ramadhan; Ida Adhayanti; Hana Chen (Pharmacia)
The proper use of medications in managing diabetes mellitus (DM) is essential for achieving the best therapeutic results. Assessing the alignment of drug prescriptions with therapeutic algorithms plays a vital role in ensuring effective treatment for DM patients. This study aims to evaluate the appropriateness of medication use in DM patients according to therapeutic algorithms at community health centers (CHCs) in Makassar City, Indonesia. A cross-sectional study was conducted at five CHCs, involving 299 DM patients, including 108 males and 191 females. Data on demographics (gender, age, education, and occupation) and medication use were collected. The rationality of drug use was evaluated based on indication, drug choice, dosage, and patient suitability. Biguanides, especially metformin, were the most frequently used drugs (60.3%), followed by sulfonylureas (29%) and insulin (10.7%). The overall appropriateness of medication use according to therapeutic algorithms was 86%. However, there were shortcomings in terms of correct dosage, where approximately 30.10% of patients still received inappropriate doses. Most DM patients at the studied CHCs received medications aligned with therapeutic guidelines, demonstrating a high level of conformity in prescribing practices.